2014
DOI: 10.1111/1477-9552.12049
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Environment and Technical Efficiency: A Stochastic Frontier Analysis of Cotton Producers in West Africa

Abstract: This paper examines the effects of the institutional environment on West African cotton farmers' technical efficiency (TE). First, key aspects of the cotton sector institutional environment are discussed, including input and credit access, and producers' organisations. Then, a stochastic frontier production function, which incorporates technical inefficiency effects, is applied to farm level data collected in Benin, Burkina Faso and Mali. The survey includes farmers' evaluations of the cotton sector institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 56 publications
2
29
0
1
Order By: Relevance
“…Growers differ in farm size, income sources, resource endowment, and management abilities. For cotton production among the West Africa's C‐4, field studies indicate that some growers consistently perform better than the average while others consistently perform worse (Theriault, ). Hence by setting a single price, cotton parastatals over subsidize some producers and under subsidize others implying that the vertical integration parastatal market structure is less efficient than a free market.…”
Section: Simulated Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Growers differ in farm size, income sources, resource endowment, and management abilities. For cotton production among the West Africa's C‐4, field studies indicate that some growers consistently perform better than the average while others consistently perform worse (Theriault, ). Hence by setting a single price, cotton parastatals over subsidize some producers and under subsidize others implying that the vertical integration parastatal market structure is less efficient than a free market.…”
Section: Simulated Results and Discussionmentioning
confidence: 99%
“…This theoretical argument is supported by empirical studies. For instance, a survey of cotton producers in Burkina Faso, Mali, and Benin found that farmers with access to inputs from cotton parastatals were more productive than farmers without access to inputs (Theriault, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…(), Singbo and Oude Lansink (), Kokoye et al. (), Theriault and Serra (), Ayenew et al. (), Pede et al.…”
Section: Data Descriptionmentioning
confidence: 99%